Satyra, rozmowa zmarłych czy dialog polityczny? O formie gatunkowej utworu Klemensa Janickiego „In Polonici vestitus varietatem et inconstantiam dialogus” - Szczot, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The articles focuses on the analysis of the genology of a literary piece by Klemens Janicki. Its form turns out to be of complex and syncretic nature, likewise the issues discussed therein and concerning the politics and social manners.